Differential Contribution of Right and Left Amygdala to Affective Information Processing - Hans J. Markowitsch (Behavioural Neurology)
Evidence for a differential involvement of the human left and right amygdala in emotional and cognitive behaviour is reviewed, with a particular emphasis on functional imaging results and case reports on patients with amygdalar damage. The available evidence allows one to conclude that there is definitely a hemisphere specific processing difference between the left and right amygdala. However, between studies the direction of the asymmetry is partly incongruent. In spite of this, the following tentative proposals are made: the left amygdala is more closely related to affective information encoding with a higher affinity to language and to detailed feature extraction, and the right amygdala to affective information retrieval with a higher affinity to pictorial or image-related material. Furthermore, the right amygdala may be more strongly engaged than the left one in a fast, shallow or gross analysis of affect-related information.